United States tariff history - Smith, A.C. (My University, 1897)
Introduction: In all countries it has been found a necessity to raise money for government expenses by means of a tax on imports. It is found that this indirect tax is by far the most practical method. The duties are collected by the revenue officers hired by the government. All countries are chiefly dependent on such a tax for means to run their national affairs. This tariff question has proved itself as great a problem as ever any able body of men have cared to solve. In our country it has been amply proved so. We employ the best legislators of our country that we can procure and give their all the support we can. These men have studied diligently the needs of the country. Indeed they have been doing this for over a century but there is still this problem unsolved. We have had numerous tariff bills framed but not one which has ever proved itself satisfactory to the people for any length of time.
Citation: Smith, A.C. United States tariff history. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Economics; United States; Tariff; Theses; Manuscripts (documents)